2021
DOI: 10.1007/s00300-021-02977-3
|View full text |Cite
|
Sign up to set email alerts
|

Cetacean distribution in relation to oceanographic features at the Kerguelen Plateau

Abstract: The Kerguelen Plateau in the south-eastern Indian Ocean is one of the most isolated and understudied regions on earth. As part of the Kerguelen Plateau Drifts project, Marine Mammal Observer (MMO) data were collected during a seismic survey in the austral summer (January-February 2020). Relationships between observation effort, cetacean sightings, seismic operations, and oceanographic variables-including bathymetry (depth and slope), nutrient concentrations, and indices of primary productivity-were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Correspondingly, ice thickness was selected as a predictive factor. Additionally, Todd and Williamson (2022) found that dissolved oxygen and chlorophyll-a concentrations significantly influenced cetacean occurrence; thus, these two factors were included. Hydrographic conditions such as mixing, upwelling, and frontogenesis normally promote high primary productivity, which leads to higher concentrations of prey, attracting more common minke whales to forage in a given area.…”
Section: Environmental Predictor Variablesmentioning
confidence: 99%
“…Correspondingly, ice thickness was selected as a predictive factor. Additionally, Todd and Williamson (2022) found that dissolved oxygen and chlorophyll-a concentrations significantly influenced cetacean occurrence; thus, these two factors were included. Hydrographic conditions such as mixing, upwelling, and frontogenesis normally promote high primary productivity, which leads to higher concentrations of prey, attracting more common minke whales to forage in a given area.…”
Section: Environmental Predictor Variablesmentioning
confidence: 99%
“…Although its northernmost range includes Aotearoa New Zealand, where it is considered a taonga (treasured) species by iwi Māori (Māori tribes), the hourglass dolphin is strongly associated with the Antarctic Convergence, and rarely found in close proximity to land masses (Acevedo, Garthe, and González 2017;Dellabianca et al 2012;Santora 2012). Although not an uncommon species (Goodall et al 1997), due to the remoteness and difficulty of surveying Antarctic waters, it is one of the least studied species of dolphin (Dellabianca et al 2012;Goodall et al 1997), with information largely limited to observations from living animals: group size, locality, acoustics, and presence of calves (Goodall 1997;Acevedo, Garthe, and González 2017;Dellabianca et al 2012;Tougaard and Kyhn 2009;Kyhn et al 2009;Thiele, Chester, and Gill 2000;Todd and Williamson 2022).…”
Section: Introductionmentioning
confidence: 99%